Evaluating of the reasons for absenteeism in terms of different variables according to their own perceptions of pre-service teachers - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
The aim of this study is to reveal the reasons of absenteeism in terms of different variables according to pre-service teachers. The research is a quantitative research which is designed on survey method. Population of the study consist of pre-service teachers who maintain education in the faculty of education at the universities in the 2008-2009 academic year and samples include 308 pre-service teachers who study at Faculty of Education at Rize University. 'Scale of Absenteeism Reasons' which has been developed by the researchers has been used as an instrument for collecting data. In the statistical transactions, independent-samples t test, frequency analysis and One Way Anova have been applied. At the end of the factor analysis, the scale has been reduced to 15 items and its reliability coefficient has been calculated to be as .815. At the end of the research, it has been determined that there is meaningful difference between the reasons of absenteeism and class and gender variables. There is no meaningful difference between the reasons of absenteeism and environment. Furthermore, it has been seen that the reasons of absenteeism have varied between the students who have higher success and who have lower success at school. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Absenteeism; reasons of absenteeism; pre-service teachers; success; academic success; PERFORMANCE; STUDENTS